2003
DOI: 10.1507/endocrj.50.689
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physiologic Hyperinsulinemia during an Oral Glucose Tolerance Test on the Levels of Dehydroepiandrosterone (DHEA) and Its Sulfate (DHEAS) in Healthy Young Adults Born with Low and with Normal Birth Weight

Abstract: Abstract. Several data support that adrenal hyperandrogenism affects women with low birth weight (LBW). We also found an association between serum dehydroepiandrosterone (DHEA) and fasting insulin levels. The aim of our study was to detect the acute effects of reactive hyperinsulinemia during oral glucose tolerance test (OGTT) on DHEA(S) levels in LBW men and women. Fifty three men and 47 women (of those, 37 men and 33 women were LBW) were enrolled. DHEA, DHEAS, and insulin levels were measured before and duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Serum DHEA and dehydroepiandrosterone sulphate (DHEA-S) levels were determined by direct radio-immunoassay as described previously [28] .…”
Section: Serum Biochemistrymentioning
confidence: 99%
“…Serum DHEA and dehydroepiandrosterone sulphate (DHEA-S) levels were determined by direct radio-immunoassay as described previously [28] .…”
Section: Serum Biochemistrymentioning
confidence: 99%
“…We have also shown an increased prevalence of glucose intolerance in women with idiopathic hirsutism, who actually have normal serum androgen levels (12). From another point of view it has been shown that hyperinsulinemia during OGTT might activate the androgen pathway of the adrenal cortex (18). In the present study, we have also investigated the prevalence of glucose intolerance and the presence or absence of insulin resistance in patients with IHA.…”
Section: Discussionmentioning
confidence: 57%
“…Recent human studies on the effect of hyperinsulinemia on AA production and metabolism have demonstrated divergent results (33)(34)(35)(36). These results may be due to the variability of the populations studied.…”
Section: Discussionmentioning
confidence: 99%